Development vectors of foreign library science at present stage - P. S. Romanoff (Библиосфера, 2011)
Both external and internal factors influencing on the development of a modern library are considered. These factors are determined by globalization processes in modern society. In such circumstances, the development of foreign librarianship becomes increasingly interdisciplinary. The views of foreign specialists in librarianship are rather controversial, but nevertheless, theoretical researches and practical activities of foreign libraries have a strong purpose to prove the right of library to exist in the information society, to adopt the profession as a librarian as a necessary one in socio-economic continuum, to provide public the undeniable proof of a highly effective library work in new economic conditions, that is to prove the efficiency of its work.